On the frontline of the welfare service state: any possibilities for a practice of citizenship? - Urban Nothdurfter (Social Work and Society)
The article starts from the broad shift towards active service-oriented welfare states highlighting its underlying ideas and main characteristics in order to discuss critical implications of this mode of welfare state intervention to the notion of social citizenship. This perspective is important to point out the critical role of frontline work in this context. Frontline practitioners hold a key dimension of citizenship, especially in contexts of active service-oriented welfare states with their strong emphasis on service provision and higher degrees of lower-level and frontline discretion. Based on contributions from street-level research in activation services, the article highlights critical aspects and challenges frontline practitioners have to deal with. Against this background, the contribution asks for constraints and possibilities for frontline work as a practice of citizenship. To conclude, the article underlines the need for more efforts to relate the micro-level of frontline practice with the macro-level of welfare state development. This is important not just in order to better describe and contextualize what is playing out on the street-level but also in order to address the normative questions of which policy options should come to the fore in the interaction with citizens as service users.